Studies on permeability of sisal fibre mat during thermoset resin filling in vacuum infusion process. (17th June 2015) - Subbiah, Rajkumar; Tjong, Jimmy; Nayak, Sanjay K.; Sain, Mohini
Abstract The focus of this study is contemplating the resin flow behaviour (dictating permeability) in a sisal based natural fibre mat compared to a glass fibre mat. This mainly deploys fibre reinforced plastics subjected to a vacuum infusion process. The outcome of this research emphasizes the wetting mechanism and fibre network of sisal mats, which significantly reduces the flow characteristics. In addition, it is observed that the swelling phenomenon had an insignificant or minimal influence on the permeability of the sisal fibre mat. However, employment of bio‐based resin provides a considerable change in the swelling phenomenon. Hence, this factor is important to consider in permeability studies to attain higher accuracy.